Alibis of empire - "Mantena, Karuna" (Ranikhet, 2010)
Alibis of Empire presents a novel account of the origins, substance and afterlife of late imperial ideology. Karuna Mantena challenges the idea that Victorian empire was primarily legitimated by liberal notions of progress and civilization. In fact, as the British Empire gained its farthest reach, its ideology was being dramatically transformed by a self-conscious rejection of the liberal model. The collapse of liberal imperialism enabled a new culturalism that stressed the dangers and difficulties of trying to civilize the natives. And, hand in hand with this shift in thinking was a shift in practice toward models of indirect rule. Mantena shows that the work of the Victorian legal scholar Henry Maine was at the centre of these momentous changes. Alibis of Empire examines how Maine's sociotheoretic model of traditional society laid the groundwork for the culturalist logic of late empire. In charting the movement from liberal idealism, through culturalist explanation, to retroactive alibi within nineteenth-century British imperial ideology, Alibis of Empire unearths a striking and pervasive dynamic of modern empire.
Keywords: Political ideology-Henry Maine